Finance and Development, March 2020. (Finance and Development; Finance and Development, 2020)
This issue of Finance and Development discusses link between demographics and economic well-being. In the coming decades, demographics is expected to be more favorable to economic well-being in the less developed regions than in the more developed regions. The age structure of a population reflects mainly its fertility and mortality history. In high-mortality populations, improved survival tends to occur disproportionately among children. The 'demographic dividend' refers to the process through which a changing age structure can spur economic growth. It depends, of course, on several complex factors, including the nature and pace of demographic change, the operation of labor and capital markets, macroeconomic management and trade policies, governance, and human capital accumulation. Population aging is the dominant demographic trend of the twenty-first century-a reflection of increasing longevity, declining fertility, and the progression of large cohorts to older ages. Barring a change in current trends, the industrial world's working-age population will decline over the next generation, and China's working-age population will decline as well. At the same time, trends toward increased labor force participation of women have played out with, for example, more women than men now working in the United States.